Loss of the Dβ1 nicotinic acetylcholine receptor subunit disrupts bursicon-driven wing expansion and diminishes adult viability in Drosophila melanogaster. Issue 1 (13th July 2021) - Christesen, Danielle; Yang, Ying Ting; Chen, Wei; Batterham, Philip; Perry, Trent
Abstract: Cholinergic signaling dominates the insect central nervous system, contributing to numerous fundamental pathways and behavioral circuits. However, we are only just beginning to uncover the diverse roles different cholinergic receptors may play. Historically, insect nicotinic acetylcholine receptors have received attention due to several subunits being key insecticide targets. More recently, there has been a focus on teasing apart the roles of these receptors, and their constituent subunits, in native signaling pathways. In this study, we use CRISPR-Cas9 genome editing to generate germline and somatic deletions of the D β 1 nicotinic acetylcholine receptor subunit and investigate the consequences of loss of function in Drosophila melanogaster . Severe impacts on movement, male courtship, longevity, and wing expansion were found. Loss of D β 1 was also associated with a reduction in transcript levels for the wing expansion hormone bursicon . Neuron-specific somatic deletion of D β 1 in bursicon -producing neurons ( CCAP -GAL4) was sufficient to disrupt wing expansion. Furthermore, CCAP -GAL4-specific expression of D β 1 in a germline deletion background was sufficient to rescue the wing phenotype, pinpointing CCAP neurons as the neuronal subset requiring D β 1 for the wing expansion pathway. Dβ1 is a known target of multiple commercially important insecticides, and the fitness costs exposed here explain why field-isolated target-site resistance has only been reported for amino acid replacements and not loss of function. This work reveals the importance of Dβ1-containing nicotinic acetylcholine receptors in CCAP neurons for robust bursicon -driven wing expansion.